A DMAIC-Based Six Sigma Analysis in Culinary MSMEs: A Case Study of Refresh Seafood - Camelia Rizki Agrina; Chelsea Ananda Balqis; Ghina Ayu Larasati (International Journal of Management and Business Economics, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector frequently face operational quality challenges, particularly service time variability, raw material waste, and limited capacity during demand surges. These problems are largely driven by process variation rather than defects in final products, especially in micro-scale enterprises with limited quantitative data. This study aims to analyze operational quality issues at Refresh Seafood, a micro-scale culinary MSME, using the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, and Control) approach, and to formulate practical improvement strategies aligned with MSME characteristics. A descriptive qualitative approach was employed through semi-structured interviews and direct observation. Data were analyzed using the DMAIC framework supported by qualitative indicators and fishbone analysis. The findings reveal that service time instability between dine-in and delivery orders, suboptimal raw material utilization, and reactive capacity management are the main quality issues. Proposed improvements include developing mini standard operating procedures (SOPs), optimizing order flow, implementing batch preparation during peak periods, and utilizing leftover raw materials. This study demonstrates that Six Sigma can be flexibly applied in micro-scale culinary MSMEs to improve process stability and service efficiency.